A novel hACE2 knock-in mouse model recapitulates pulmonary and intestinal SARS-CoV-2 infection - Zhou, Xiaoyang; Sun, Weiyang; Zhang, Yu; Gu, Hongjing; Wang, Ruixuan; Xie, Peng; Zhu, Yunkai; Qiu, Minyue; Ding, Xiaoyan; Wang, Hui; Gao, Yuwei; Li, Jintao (Frontiers in Microbiology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is responsible for the coronavirus disease 2019 (COVID-19) pandemic. Angiotensin-converting enzyme 2 (ACE2) is expressed in the gastrointestinal tract and a receptor for SARS-CoV-2, making the gastrointestinal tract a potential infection site. Multiple studies have indicated that an increasing number of COVID-19 patients presented with gastrointestinal symptoms that are highly associated with disease severity. Moreover, emerging evidence has demonstrated that alterations in the gut immune microenvironment induced by intestinal SARS-CoV-2 infection can regulate respiratory symptoms. Therefore, targeting the intestines may be a candidate therapeutic strategy in patients with COVID-19; however, no mouse model can serve as an appropriate infection model that can develop fatal pneumonia while mimicking intestinal infection. In this study, a novel human ACE2 knock-in (KI) mouse model (abbreviated as hACE2-KI) was systemically compared with the popular K18-hACE2 mice, which showed differences in the distribution of lung and intestinal infections and pathophysiological characteristics. These new hACE2-KI mice were more susceptible to intranasal infection with SARS-CoV-2, and the mice not only developed mild to severe lung injury, but also acquired intestinal infection. Consequently, this model can be a useful tool for studying intestinal SARS-CoV-2 infection and developing effective therapeutic strategies.